Ketahanan Wilayah Kabupaten Karimun Dalam Menghadapi Pandemi Covid-19 - Diky Budiman; Asa Bintang Kapiarsa (Universitas Gadjah Mada, 2021)
This research will open up a new discussion regarding the resilience of a region in facing the Covid-19 Pandemic. Aim of this researcher is to depict vulnerability of the region towards pandemic Covid-19. The analysis of this research uses a descriptive qualitative approach with spatial identification and literature review. From the literature review, there are 5 factors of defense geography that can be used to identified regional vulnerability, which are secure location, topographical depression, population density, land use and distribution of health services. Based on the results obtained, it is known that there are some regions that have Tinggi vulnerability and yet still struggling in facing the Pandemic Covid-19 such as Karimun and Kundur. But there are also regions that have Tinggi vulnerability but can push down the spreading such as Moro, Durai,Meral, Meral Barat and Tebing Subdistricts. Some other regions that have Sedang and Rendah vulnerability also can deal with pandemic very well.